2010
DOI: 10.3390/ijerph7052071
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of the Conchos River in Mexico: Does It Pose a Health Risk to Local Residents?

Abstract: Presently, water contamination issues are of great concern worldwide. Mexico has not escaped this environmental problem, which negatively affects aquifers, water bodies and biodiversity; but most of all, public health. The objective was to determine the level of water contamination in six tributaries of the Conchos River and to relate their levels to human health risks. Bimonthly samples were obtained from each location during 2005 and 2006. Physical-chemical variables (temperature, pH, electrical conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
1
6
1
16
Order By: Relevance
“…This effect is shown in Figure 10 where the mean of Ni before the Holy Week vacation period was 1.01 ppm, and this element increased to 1.77 ppm after the Holy Week vacation period. The values reported in this study relative to element Ni are higher than previously reported where it was found at 0.47 mg L –1 as the most contaminated location [19]. In addition, Ni values are higher than the findings of Holguin et al .…”
Section: Resultscontrasting
confidence: 90%
“…This effect is shown in Figure 10 where the mean of Ni before the Holy Week vacation period was 1.01 ppm, and this element increased to 1.77 ppm after the Holy Week vacation period. The values reported in this study relative to element Ni are higher than previously reported where it was found at 0.47 mg L –1 as the most contaminated location [19]. In addition, Ni values are higher than the findings of Holguin et al .…”
Section: Resultscontrasting
confidence: 90%
“…Qian et al [11] found an increase in the physicalchemical variables during the rainy season, and consequently low levels of water quality. This is because some rain is acidic or can have more diluted contaminants [27]. Varnosfaderany et al [50] estimated a WQI for an ecosystem of an arid zone and found lower levels in August, which they attributed to agricultural activities that increase FC and DBO concentrations in water.…”
Section: Water Quality Index (Wqi)mentioning
confidence: 99%
“…In the case of Mexico, there have been some studies concerning water pollution in the Conchos watershed, the Development of a Water Quality Index (WQI) of an Artificial Aquatic Ecosystem in Mexico 1297 most important watershed in the State of Chihuahua [24] as well as in tributaries like the San Pedro River [25]. The studies detected varying levels of pollution in the rivers and other water ecosystems in Chihuahua [26][27][28]. For instance, Gutierrez et al [29] determined contamination levels in the San Pedro River and the Francisco I Madero Dam.…”
Section: Introductionmentioning
confidence: 99%
“…Zn potential health concerns when detected in drinking water and in different aquatic environments [59][60][61][62]. The detection limits and the accuracy of analytical results are of prime importance.…”
Section: Selected Prominent Lines Wavelength Nmmentioning
confidence: 99%